LAYANAN BIMBINGAN DAN KONSELING ANAK BERKEBUTUHAN KHUSUS (AUTIS) DI SKHN 02 KOTA SERANG - Nur faridah; Yahdinil Firda Nadirah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This descriptive-qualitative study examines guidance and counseling services for autistic students at an inclusive school in Serang. Data were collected through observation and interviews to gain in-depth information about these services. Basic guidance and counseling services aim to help all students, including autistic students, develop life skills. Learning begins at the beginning of the school year and is tailored to the age and development of the autistic students.